2022
DOI: 10.3389/fmars.2022.838967
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Eelgrass and Macroalgae in Pacific Northwest Estuaries Following an Unprecedented NE Pacific Ocean Marine Heatwave

Abstract: The 2013-2016 northeast Pacific Ocean marine heatwave (MHW) had myriad impacts on marine communities, but little is known about how this event affected coastal estuaries. We examined the extent to which elevated temperatures associated with the offshore MHW were observed in four estuaries (Willapa Bay, Washington and Netarts Bay, Yaquina Bay, and Coos Bay, Oregon) and the responses of macrophytes at marine dominated sites within these estuaries. Records of eelgrass (Zostera marina), ulvoid macroalgae (Ulva and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 83 publications
2
16
0
Order By: Relevance
“…Previously, Thom et al (2003) showed that stations in the Coos Estuary closer to the mouth had higher values of eelgrass density (100-200 shoots per m 2 ) related to the influence of oceanic, low-turbidity waters, while stations farther away from the mouth of the estuary had smaller density, related to increased turbidity due to the input of freshwater. A similar result was found across multiple PNW estuaries by Magel et al (2022). Thom et al (2003) also suggested that eelgrass decline was correlated with anomalously warm waters during the 1997-1998 El Niño; the degree to which this happens again between 2014-2016 is the subject of this study (Figure 1).…”
Section: Study Areasupporting
confidence: 77%
See 4 more Smart Citations
“…Previously, Thom et al (2003) showed that stations in the Coos Estuary closer to the mouth had higher values of eelgrass density (100-200 shoots per m 2 ) related to the influence of oceanic, low-turbidity waters, while stations farther away from the mouth of the estuary had smaller density, related to increased turbidity due to the input of freshwater. A similar result was found across multiple PNW estuaries by Magel et al (2022). Thom et al (2003) also suggested that eelgrass decline was correlated with anomalously warm waters during the 1997-1998 El Niño; the degree to which this happens again between 2014-2016 is the subject of this study (Figure 1).…”
Section: Study Areasupporting
confidence: 77%
“…Our results suggest that the MHWs and increased air temperature contributed to the eelgrass density decline in 2015 (Figures 3, 10, Supplementary Figure 4). In contrast, Magel et al (2022) show an increase in eelgrass at one annually-surveyed station (Barview, see Figure 9) closer to the main channel than Valino Island. Their results show an increase in eelgrass density and biomass during the summer of 2015 and summer of 2016, followed by a decline to longer term average values.…”
Section: Effects On Eelgrass (Zostera Marina)mentioning
confidence: 87%
See 3 more Smart Citations